2020
DOI: 10.21037/cco.2020.01.06
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of neoadjuvant/adjuvant chemotherapy for breast cancer

Abstract: Biomarkers and subtypes of breast cancerBreast cancer is not a single disease. Clinically, breast cancer has been known to have distinct prognosis and response to chemotherapies based on the immunohistochemical (IHC) subtypes [e.g., estrogen receptor (ER), progesterone receptor (PgR), and human epidermal growth factor receptor 2 (HER2)] (1,2). hormone receptor (HR)-positive (ER and/or PgR-positive)/HER2-negative breast cancers have a good response to hormone therapy and favourable prognosis. HER2-positive and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 40 publications
(56 reference statements)
0
35
0
3
Order By: Relevance
“…Therefore, it is more reasonable to divide patients into low (<50%) and high (≥50%) groups. 20,[23][24][25][26][27][28][29][30][31] Previous studies have reported that low TIL cases exhibited significantly lower ADC values than high TIL cases. 32,35 Interestingly, this is not consistent with our results, as these previous studies excluded the non-mass-like lesions, and as the differences in the size and placement of ROIs may change the ADC values.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, it is more reasonable to divide patients into low (<50%) and high (≥50%) groups. 20,[23][24][25][26][27][28][29][30][31] Previous studies have reported that low TIL cases exhibited significantly lower ADC values than high TIL cases. 32,35 Interestingly, this is not consistent with our results, as these previous studies excluded the non-mass-like lesions, and as the differences in the size and placement of ROIs may change the ADC values.…”
Section: Discussionmentioning
confidence: 98%
“…Increasing evidence shows the extent of which TILs are known to have predictive value for NAC and prognostic value in breast cancer, especially in TNBC and HER2-positive breast cancer patients. [23][24][25][26][27][28][29][30][31] Therefore, an accurate preoperative evaluation method of TIL level from noninvasive imaging data may help guide treatment regimens. Our study demonstrated that a radiomics nomogram based on preoperative MRI that incorporates optimal clinical factors and a radiomics signature exhibited the best performance for the evaluation of TIL level.…”
Section: Discussionmentioning
confidence: 99%
“…The combined application of docetaxel, cyclophosphamide and epirubicin can significantly improve the effect of chemotherapy, increase the CR rate of tumor and enhance the survival of relevant patients. In addition to a role in killing tumor cells, neoadjuvant chemotherapy can also promote the transformation of tumor cells into normal breast cells, so as to gradually restore the expression of ER, HER-2, SATB1 and other indexes to the normal range 17 However, it should be noted that the immune dysfunction caused by chemotherapy will also result in immunosuppression of patients and reduce the therapeutic effect. In view of previous investigation, Pop et al 18 believed that neoadjuvant chemotherapy combined with immunotherapy could achieve a relatively higher pathological complete remission rate.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decades, more and more biomarkers have been found for the diagnosis and treatment of cancer [22,23]. However, the key regulatory factors in BRCA microenvironment and changes of TME in BRCA progression are yet to be clari ed.…”
Section: Discussionmentioning
confidence: 99%